2016
DOI: 10.1016/j.sleep.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in sleep: the role of neighborhood disadvantage

Abstract: Objective Disparities in sleep duration and efficiency between Black/African American (AA) and White/European American (EA) adults are well-documented. The objective of this study was to examine neighborhood disadvantage as an explanation for race differences in objectively measured sleep. Methods Data were from 133 AA and 293 EA adults who participated in the sleep assessment protocol of the Midlife in the United States (MIDUS) study (57% female; Mean Age = 56.8 years, SD=11.4). Sleep minutes, onset latency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 87 publications
(104 reference statements)
1
36
0
Order By: Relevance
“…It is pertinent that the large majority of these population-based studies relied on self-reported information on sleep duration, which may be biased by the individuals' tendency to overestimate sleep, and only moderately correlates with sleep quantity as determined from actigraphy or polysomnography [30]. Nevertheless, divergent ethnic-dependent sleep durations are apparent, and possibly amplified, also when considering objective sleep measures [28,[31][32][33][34][35]. In the Multi-Ethnic Study of Atherosclerosis (MESA), actigraphyderived habitual sleep duration in Blacks was the lowest amid all racial/ethnic groups, with 43.4% of them sleeping less than 6 hours (vs 19.3% of White) [28].…”
Section: Epidemiology Of Sleep Deficiency In Blacks/african-americansmentioning
confidence: 99%
“…It is pertinent that the large majority of these population-based studies relied on self-reported information on sleep duration, which may be biased by the individuals' tendency to overestimate sleep, and only moderately correlates with sleep quantity as determined from actigraphy or polysomnography [30]. Nevertheless, divergent ethnic-dependent sleep durations are apparent, and possibly amplified, also when considering objective sleep measures [28,[31][32][33][34][35]. In the Multi-Ethnic Study of Atherosclerosis (MESA), actigraphyderived habitual sleep duration in Blacks was the lowest amid all racial/ethnic groups, with 43.4% of them sleeping less than 6 hours (vs 19.3% of White) [28].…”
Section: Epidemiology Of Sleep Deficiency In Blacks/african-americansmentioning
confidence: 99%
“…In a recent study, Black youth who lived in predominantly White areas reported more PRD than those who lived in predominantly Black areas [ 48 ]. Place is shown to be linked to PRD [ 49 , 50 , 51 , 52 ], sleep [ 53 ], distress [ 54 , 55 ], stress [ 56 ], suicide [ 57 ], and depression [ 58 ]. SES aspects of the neighborhood, racial composition, physical and social environment, and segregation are all neighborhood and contextual factors that have mental health implications [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has documented racial disparities in sleep 12,47 but relatively few studies have examined how neighborhood characteristics might explain these disparities. 48,49 In addition to neighborhood disorder, neighborhood-level demographic characteristics accounted for a portion of racial/ethnic bedtime disparities in our models, especially among black children. These findings are important, as they suggest that black-white sleep disparities during childhood are partly rooted in dissimilar environmental conditions.…”
Section: Discussionmentioning
confidence: 99%